Surface-treated copper foil, copper-clad laminate, and printed wiring board

By forming a surface treatment layer with a specific volume of solid parts on the surface of the copper foil, the problem of insufficient adhesion between the copper foil and the resin substrate in the high-frequency region is solved, and lower conductor losses and better signal transmission performance are achieved.

CN119452123APending Publication Date: 2025-02-14JX NIPPON MINING & METALS CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380048671.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-28
Filing Date
2023-08-07
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the adhesion between copper foil and resin substrate in high-frequency regions, resulting in increased conductor loss and dielectric loss, affecting signal transmission.

Method used

By forming a surface treatment layer on the surface of the copper foil, the volume Vmc of the solid portion of the core part is controlled within the range of 0.35 to 0.55 μm3/μm2 to improve the anchoring effect and improve the adhesion.

Benefits of technology

In high-frequency use, the adhesion between copper foil and resin substrate is significantly improved, conductor losses are reduced, and the performance of copper clad laminated plate and printed wiring board is optimized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119452123A_ABST
    Figure CN119452123A_ABST
Patent Text Reader

Abstract

The present invention relates to a surface-treated copper foil having a copper foil and a surface-treated layer formed on at least one surface of the copper foil. The solid part volume Vmc of the core part of the surface treatment layer is 0.35-0.55 [mu] m < 3 > / [mu] m < 2 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a surface treated copper foil, a copper clad laminate and a printed wiring board. Background Art

[0002] Copper clad laminates are widely used in various applications such as flexible printed wiring boards. Flexible printed wiring boards are manufactured by etching the copper foil of a copper clad laminate to form a conductor pattern (also called a "wiring pattern"), and connecting and mounting electronic components on the conductor pattern using solder.

[0003] In recent years, in electronic devices such as computers and mobile terminals, as communication speeds increase and capacitance increases, electrical signals continue to increase in frequency, and the industry requires flexible printed wiring boards that can cope with this. In particular, the higher the frequency of the electrical signal, the greater the loss (attenuation) of the signal power, and the more difficult it is to read the data. Therefore, the industry requires reducing the loss of signal power.

[0004] There are two main reasons why signal power loss (transmission loss) occurs in electronic circuits. The first is conductor loss, which is the loss caused by copper foil. The second is dielectric loss, which is the loss caused by the resin substrate.

[0005] In the high frequency region, the current has the characteristic of flowing on the conductor surface (i.e., skin effect). Therefore, if the surface of the copper foil is rough, the current will flow along a complex path. Therefore, in order to reduce the conductor loss of high-frequency signals, it is more ideal to reduce the surface roughness of the copper foil. Hereinafter, in this specification, when only "transmission loss" and "conductor loss" are recorded, it mainly means "transmission loss of high-frequency signals" and "conductor loss of high-frequency signals".

[0006] Dielectric loss depends on the type of resin substrate. Therefore, in a circuit substrate where high-frequency signals flow, it is more desirable to use a resin substrate formed of a low-dielectric material (e.g., liquid crystal polymer, low-dielectric polyimide). In addition, dielectric loss is also affected by the "adhesive that bonds the copper foil to the resin substrate." Therefore, it is more desirable to bond the copper foil to the resin substrate without using an adhesive.

[0007] Therefore, in order to bond the copper foil to the resin substrate without using an adhesive, it is proposed to form a surface treatment layer on at least one side of the copper foil. For example, Patent Document 1 discloses a method of providing a roughening treatment layer formed of roughening particles on the copper foil and forming a silane coupling treatment layer on the outermost layer.

[0008] [Prior art literature]

[0009] [Patent Document]

[0010] [Patent Document 1] Japanese Patent Application Publication No. 2012-112009. Summary of the invention

[0011] [Problems to be Solved by the Invention]

[0012] If the copper foil surface is roughened, the anchoring effect of the roughened particles can be used to improve the adhesion between the copper foil and the resin substrate, but the conductor loss may increase due to the skin effect. Therefore, it is more desirable to reduce the roughened particles electrodeposited on the copper foil surface.

[0013] On the other hand, if the coarsening particles deposited on the surface of the copper foil are reduced, the anchoring effect brought about by the coarsening particles decreases. As a result, the adhesion between the copper foil and the resin substrate cannot be fully obtained. In particular, compared with the previous resin substrate, the resin substrate formed by low dielectric materials such as liquid crystal polymers and low dielectric polyimides is difficult to adhere to the copper foil, so it is desired to develop a method for improving the adhesion between the copper foil and the resin substrate.

[0014] Furthermore, although the silane coupling treatment layer has an effect of improving the adhesion between the copper foil and the resin substrate, the effect of improving the adhesion may be insufficient depending on the type of the layer.

[0015] The present invention is made to solve the above-mentioned problems. In one embodiment, the present invention aims to provide a surface-treated copper foil that can improve adhesion with a resin substrate, especially a resin substrate suitable for high-frequency applications.

[0016] In another embodiment, an object of an embodiment of the present invention is to provide a copper-clad laminate having excellent adhesion between a resin substrate, especially a resin substrate suitable for high-frequency applications, and a surface-treated copper foil.

[0017] Furthermore, in still another embodiment, an object of an embodiment of the present invention is to provide a printed wiring board having excellent adhesion between a resin substrate, particularly a resin substrate suitable for high-frequency applications, and a circuit pattern.

[0018] [Technical means to solve the problem]

[0019] In order to solve the above-mentioned problems, the inventors of the present invention have conducted intensive research on surface-treated copper foil. As a result, it is found that based on the understanding that the solid volume Vmc of the core part of the surface treatment layer is related to the surface shape of the surface treatment layer (especially the size of the roughened particles in the roughening treatment layer), by controlling the solid volume Vmc of the core part of the surface treatment layer within a specific range, the anchoring effect brought by the surface treatment layer can be enhanced, thereby improving the adhesion between the surface-treated copper foil and the resin substrate.

[0020] That is, in one embodiment, the embodiment of the present invention relates to a surface-treated copper foil, which comprises a copper foil and a surface-treated layer formed on at least one side of the copper foil, and the solid volume Vmc of the core part of the surface-treated layer is 0.35 to 0.55 μm 3 / μm 2 .

[0021] In another embodiment, the present invention relates to a copper-clad laminate comprising the surface-treated copper foil and a resin substrate formed on the surface-treated layer of the surface-treated copper foil.

[0022] Furthermore, in still another example, an embodiment of the present invention is directed to a printed wiring board including a circuit pattern formed by etching the surface-treated copper foil of the copper-clad laminate.

[0023] [Effects of the Invention]

[0024] According to an embodiment of the present invention, in one example, a surface-treated copper foil capable of improving adhesion to a resin substrate, especially a resin substrate suitable for high-frequency applications, can be provided.

[0025] According to another embodiment of the present invention, a copper-clad laminate having excellent adhesion between a resin substrate, especially a resin substrate suitable for high-frequency applications, and a surface-treated copper foil can be provided.

[0026] Furthermore, according to an embodiment of the present invention, in another example, a printed wiring board having excellent adhesion between a resin substrate, especially a resin substrate suitable for high-frequency applications, and a circuit pattern can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] [ Figure 1 ] is a graph showing a typical load curve of a surface treatment layer.

[0028] [ Figure 2 ] is a cross-sectional view schematically showing an example of an implementation scheme of the present invention, namely, a surface-treated copper foil having a roughening treatment layer on one side of the copper foil. DETAILED DESCRIPTION

[0029] Hereinafter, the preferred embodiments of the present invention will be specifically described, but the present invention should not be limited to these embodiments and interpreted, and various changes and improvements can be made based on the knowledge of the industry within the scope of the gist of the present invention. The multiple components disclosed in the following embodiments can form various inventions by appropriate combination. For example, a part of the components can be deleted from all the components shown in the following embodiments, and the components of different embodiments can also be appropriately combined.

[0030] The surface-treated copper foil according to an embodiment of the present invention comprises a copper foil and a surface-treated layer formed on at least one surface of the copper foil, wherein a core portion of the surface-treated layer has a substantial volume Vmc of 0.35 to 0.55 μm 3 / μm 2 .

[0031] According to the above configuration, it is possible to realize a surface-treated copper foil capable of improving adhesion to a resin substrate, particularly a resin substrate suitable for high-frequency applications.

[0032] The surface treatment layer may be formed on only one side of the copper foil or on both sides of the copper foil. When the surface treatment layer is formed on both sides of the copper foil, the types of the surface treatment layers may be the same or different. When the types of the surface treatment layers formed on both sides of the copper foil are different, for example, a surface treatment layer including a roughening treatment layer is formed on one side of the copper foil, and a surface treatment layer not including a roughening treatment layer is formed on the other side of the copper foil.

[0033] The surface shape of the surface treatment layer can be determined using surface texture parameters. The surface texture parameters are obtained by measuring the surface shape in accordance with ISO 25178-2:2012 and analyzing a load curve calculated from the measurement data.

[0034] When explaining the load curve, first, the load area ratio will be explained.

[0035] The load area ratio is a ratio obtained by dividing the area corresponding to the cross section of a three-dimensional object to be measured by the measurement field area when the object to be measured is cut at a certain height. In the present invention, copper foil or a surface treated layer of surface treated copper foil is assumed as the object to be measured.

[0036] The load curve is a curve showing the load area ratio at each height. The height near the load area ratio of 0% shows the height of the highest part of the measured object. The height near the load area ratio of 100% shows the height of the lowest part of the measured object.

[0037] Figure 1 is a graph showing a typical load curve for a surface treatment layer.

[0038] The load curve can be used to express the solid volume and space volume of the surface treatment layer. The solid volume is equivalent to the volume of the solid part of the measured object in the measurement field of view. The space volume is equivalent to the volume of the space between the solid parts in the measurement field of view.

[0039] In the load curve described in the present invention, the load curve is divided into a valley portion, a core portion, and a mountain portion with the positions where the load area ratio is 10% and 80% as boundaries.

[0040] Reference Figure 1, and at the same time, each parameter is described corresponding to the surface treatment layer of the embodiment of the present invention. Vvv refers to the spatial volume of the valley of the surface treatment layer, Vvc refers to the spatial volume of the core of the surface treatment layer, Vmp refers to the solid volume of the mountain of the surface treatment layer, and Vmc refers to the solid volume of the core of the surface treatment layer. Sk refers to the level difference of the core of the surface treatment layer (the difference between the upper limit level and the lower limit level of the core), Spk refers to the average height of the mountain of the surface treatment layer, and Svk refers to the average depth of the valley of the surface treatment layer.

[0041] Furthermore, the mountain refers to the part of the object with a higher height. The valley refers to the part of the object with a lower height. The core refers to the part of the object excluding the mountain and valley, that is, the part with a height close to the average.

[0042] The solid volume Vmc of the core of the surface treatment layer (hereinafter sometimes referred to as "Vmc") is related to the surface shape of the surface treatment layer. In particular, when the surface treatment layer includes a roughening treatment layer, it is related to the size of the roughening particles constituting the roughening treatment layer.

[0043] As described above, in the surface-treated copper foil according to the embodiment of the present invention, Vmc of the surface-treated layer is specified to be 0.35 to 0.55 μm. 3 / μm 2 In particular, when the surface treatment layer includes a roughening treatment layer, if the Vmc is within this range, the size (height and width) of the roughening particles is within an appropriate range, and when the surface treatment layer is bonded to the resin substrate, the roughening particles are not easily damaged, thereby enhancing the anchoring effect. If the Vmc of the surface treatment layer is 0.35 μm 3 / μm 2 If the Vmc of the surface treatment layer is 0.55 μm 3 / μm 2 The transmission loss can be reduced.

[0044] From the viewpoint of stably improving the anchoring effect of the surface treatment layer, the Vmc of the surface treatment layer is preferably 0.37 to 0.52 μm. 3 / μm 2 , more preferably 0.38 to 0.45 μm 3 / μm 2 .

[0045] The level difference Sk of the core part of the surface treatment layer (hereinafter sometimes referred to as "Sk") is related to the ease with which the core part (height average part) of the surface treatment layer is embedded in the resin substrate when the surface treatment layer is bonded to the resin substrate. In particular, when the surface treatment layer includes a roughening treatment layer, it is related to the ease with which the height average part of the roughening particles constituting the roughening treatment layer is embedded in the resin substrate.

[0046] When the Vmp of the surface treatment layer is within the above range, the Sk of the surface treatment layer may be 0.70 to 1.50 μm from the viewpoint of ensuring that the core of the surface treatment layer is embedded in the resin substrate. If the Sk is in this range, the anchoring effect brought about by the core of the surface treatment layer being embedded in the resin substrate can be improved, so the adhesion between the surface-treated copper foil and the resin substrate is improved. If the Sk of the surface treatment layer is above 0.70 μm, the core of the surface treatment layer is easily embedded in the resin substrate, thereby obtaining the desired anchoring effect. If the Sk of the surface treatment layer is below 1.50 μm, for example, the coarsened particles are not easily damaged, thereby obtaining the desired anchoring effect.

[0047] From the viewpoint of stably ensuring that the core portion of the surface treatment layer is embedded in the resin base material, the Sk of the surface treatment layer is more preferably 0.85 to 1.30 μm, and still more preferably 1.03 to 1.18 μm.

[0048] There are usually tiny uneven parts on the surface of the copper foil forming the surface treatment layer. For example, in the case of rolled copper foil, the oil pits formed by the rolling oil during rolling are formed as tiny concave parts on the surface. In addition, in the case of electrolytic copper foil, the grinding stripes of the drum formed during grinding will cause tiny uneven parts on the drum side surface of the electrolytic copper foil precipitated on the drum. If there are tiny uneven parts in the copper foil, for example, when forming the roughening treatment layer, the current is concentrated around the convex part and the roughening particles grow excessively. On the other hand, the current is not fully supplied around the concave part and the roughening particles are difficult to grow. As a result, coarse roughening particles are formed around the convex part of the copper foil, while the roughening particles are too small or no roughening particles are formed around the concave part of the copper foil, that is, the roughening particles on the surface of the copper foil are not formed uniformly. In the case of a surface-treated copper foil having a large number of coarse roughening particles, if a force is applied to peel the surface-treated copper foil after bonding with a resin substrate, stress is concentrated on the coarse roughening particles, which are easily broken, resulting in a decrease in adhesion to the resin substrate. In addition, in the case of a surface-treated copper foil having an insufficient size of roughening particles, the anchoring effect brought about by the roughening particles is reduced, and sometimes the adhesion between the copper foil and the resin substrate cannot be sufficiently obtained.

[0049] From the above viewpoints, the skewness Ssk of the surface treatment layer (hereinafter sometimes simply referred to as "Ssk") may be 0.10 to 1.00.

[0050] Here, Ssk is a parameter that expresses the degree of deviation (skewness) of the bar graph when a bar graph of height is made based on the average height. For example, in the case of Ssk=0.00, it means that the height distribution is symmetrical with respect to the average line. Again, in the case of Ssk>0.00, the larger the value, the more the height distribution is skewed to the lower side relative to the average line. On the contrary, in the case of Ssk<0.00, the smaller the value, the more the height distribution is skewed to the upper side relative to the average line. Therefore, the Ssk of the surface treatment layer becomes an indicator for evaluating the height distribution of the concave and convex of the surface treatment layer.

[0051] The Ssk of the surface treatment layer is 0.10 to 1.00. For example, when the surface treatment layer includes a roughened particle layer, it means that there are fewer roughened particles (i.e., coarse roughened particles) that grow excessively on the convex parts of the copper foil surface or fewer areas where roughened particles are not formed around concave parts such as oil pits on the copper foil surface.

[0052] From the viewpoint of stably ensuring the above-mentioned effect, the Ssk of the surface treatment layer is more preferably 0.30 to 0.90, and still more preferably 0.45 to 0.80.

[0053] The Ssk of the surface treatment layer can be determined by measuring the surface roughness in accordance with ISO 25178-2:2012 and analyzing a profile curve calculated from the measurement data.

[0054] The amount of Zn deposited in the surface treatment layer is not particularly limited, but is preferably 6 to 200 μm / dm 2 By controlling the Zn coating amount within this range, the solder heat resistance of the circuit pattern formed by the surface-treated copper foil can be improved. From the viewpoint of stably improving this effect, the Zn coating amount in the surface-treated layer is more preferably 82 to 200 μm / dm 2 .

[0055] The amount of Zn attached to the surface treatment layer can be measured by dissolving the surface treatment layer in 20% by mass nitric acid and using an atomic absorption spectrophotometer (manufactured by VARIAN, AA240FS) to perform quantitative analysis by atomic absorption method. In the case where the surface treatment layer is provided on both sides of the copper foil, the surface of the surface treatment layer not to be measured is protected, and then the surface treatment layer to be measured is dissolved for quantitative analysis.

[0056] The type of the surface treatment layer is not particularly limited as long as it has the above-mentioned surface shape, and various surface treatment layers known in the technical field can be used.

[0057] Examples of the surface treatment layer include a roughening treatment layer, a chemical resistance treatment layer, a heat resistance treatment layer, a chromate treatment layer, a silane coupling treatment layer, etc. These layers can be used alone or in combination of two or more. Among them, from the viewpoint of adhesion to the resin substrate, the surface treatment layer preferably contains a roughening treatment layer.

[0058] When the surface treatment layer includes one or more layers selected from the group consisting of a chemical-resistant treatment layer, a heat-resistant treatment layer, a chromate treatment layer, and a silane coupling treatment layer, these layers are preferably provided on the roughening treatment layer.

[0059] The roughening treatment layer contains roughening particles. The roughening particles may contain primary roughening particles and secondary roughening particles. The secondary roughening particles may have a chemical composition different from that of the primary roughening particles.

[0060] It is preferable that a covering plating layer is formed on at least a part of the surface of the primary roughened particle.

[0061] Figure 2 This is a cross-sectional view schematically showing a surface-treated copper foil having a roughened layer on one surface of the copper foil.

[0062] like Figure 2 As shown, an example of an embodiment of the present invention includes a roughening layer formed on one side of a copper foil (10). The roughening layer includes primary roughening particles (20), a covering plating layer (30) covering the primary roughening particles (20), and secondary roughening particles (40) formed on the covering plating layer (30). Preferably, the primary roughening particles (20) covered by the covering plating layer (30) are roughly spherical, and the secondary roughening particles (40) are formed to extend in a dendritic manner. It is believed that the surface-treated copper foil in which Vmc, Sk and Ssk are controlled within the above range has such a cross-sectional structure.

[0063] The roughened particles are not particularly limited, and may be formed of a single element selected from the group consisting of copper, nickel, cobalt, phosphorus, tungsten, arsenic, molybdenum, chromium, and zinc, or an alloy containing two or more of these elements.

[0064] The primary roughened particles are preferably made of copper or a copper alloy, particularly copper.

[0065] The secondary roughened particles are preferably formed of an alloy containing copper, cobalt, and nickel.

[0066] The cover plating layer is not particularly limited, and can be formed of copper, silver, gold, nickel, cobalt, zinc, etc. Among them, the cover plating layer is preferably formed of copper.

[0067] The roughening treatment layer can be formed, for example, by the following method: after performing a primary roughening treatment to form primary roughening particles, plating is performed to form a covering plating layer, and then a secondary roughening treatment is performed to form secondary roughening particles. By performing the roughening treatment in this way, it is easy to form a surface treatment layer having a surface shape as described above.

[0068] The formation of each particle and layer can be performed by electroplating. Specifically, the primary roughened particles can be formed by electroplating using a plating solution to which a trace amount of tungsten compound is added. The cover plating layer and the secondary roughened particles can be formed by electroplating using a plating solution containing a specific component.

[0069] The tungsten compound is not particularly limited, and for example, sodium tungstate (Na2WO4) or the like can be used.

[0070] The content of the tungsten compound in the plating solution is preferably 1 ppm or more. There may be a situation where there are micro-concave portions such as oil pits on the surface of the copper foil forming the roughening treatment layer, and the roughening particles are too small or no roughening particles are formed around the concave portions. However, if this content is used, the excessive growth of the primary roughening particles formed on the relatively smooth part of the copper foil will be suppressed, and the primary roughening particles will be easily formed around the concave portions. Furthermore, the upper limit of the content of the tungsten compound is not particularly limited, but from the perspective of suppressing the increase in resistance, it is preferably 20 ppm.

[0071] The conditions of electroplating when forming the roughening layer may be adjusted according to the electroplating apparatus used, etc., and are not particularly limited, but typical conditions are as follows. Each electroplating may be performed once or multiple times.

[0072] (Formation conditions of primary roughened particles)

[0073] Bath composition: 5-15 g / L Cu, 40-100 g / L sulfuric acid, 1-6 ppm sodium tungstate Bath temperature: 20-50 °C

[0074] Electroplating conditions: current density 30~90A / dm 2 , time 0.1~8 seconds

[0075] (Conditions for forming the overlay plating layer)

[0076] Plating solution composition: 10-30 g / L Cu, 70-130 g / L sulfuric acid

[0077] Bath temperature: 30~60℃

[0078] Electroplating conditions: current density 4.8~15A / dm 2 , time 0.1~8 seconds

[0079] (Formation conditions of secondary roughened particles)

[0080] Plating solution composition: 10-20 g / L Cu, 5-15 g / L Co, 5-15 g / L Ni

[0081] Bath temperature: 30~50℃

[0082] Electroplating conditions: current density 24~50A / dm 2 , time 0.3~0.8 seconds

[0083] The chemical treatment resistant layer and the heat treatment resistant layer are not particularly limited and can be formed of materials known in the technical field. Furthermore, the chemical treatment resistant layer sometimes also functions as a heat treatment resistant layer, so a single layer having both the functions of the chemical treatment resistant layer and the heat treatment resistant layer can be formed as the chemical treatment resistant layer and the heat treatment resistant layer.

[0084] As the chemical treatment resistant layer and / or heat treatment resistant layer, a layer containing one or more elements selected from the group consisting of nickel, zinc, tin, cobalt, molybdenum, copper, tungsten, phosphorus, arsenic, chromium, vanadium, titanium, aluminum, gold, silver, platinum group elements, iron and tantalum (in any form of metal, alloy, oxide, nitride, sulfide, etc.) can be prepared. Among them, the chemical treatment resistant layer is preferably a Co-Ni layer. The heat treatment resistant layer is preferably a Ni-Zn layer.

[0085] The chemical-resistant layer and the heat-resistant layer can be formed by electroplating. The conditions can be adjusted according to the electroplating device used and are not particularly limited. The conditions for forming the chemical-resistant layer (Co-Ni layer) and the heat-resistant layer (Ni-Zn layer) using a common electroplating device are as follows. In addition, electroplating can be performed once or multiple times.

[0086] (Chemical-resistant layer: Formation conditions of Co-Ni layer)

[0087] Plating solution composition: 1-8 g / L Co, 5-20 g / L Ni

[0088] Plating solution pH: 2-3

[0089] Bath temperature: 40~60℃

[0090] Electroplating conditions: current density 1~20A / dm 2 , time 0.3~0.6 seconds

[0091] (Heat-resistant treatment layer: Formation conditions of Ni-Zn layer)

[0092] Plating solution composition: 1~30g / L Ni, 1~30g / L Zn

[0093] Plating solution pH: 2-5

[0094] Bath temperature: 30~50℃

[0095] Electroplating conditions: current density 0.1~10A / dm 2 , time 0.1~5 seconds

[0096] The chromate treatment layer is not particularly limited, and can be formed of a material known in the technical field.

[0097] Here, in this specification, "chromate treatment layer" means a layer formed by a solution containing chromic anhydride, chromic acid, dichromic acid, chromate or dichromate. The chromate treatment layer may be a layer containing one or more elements selected from the group consisting of cobalt, iron, nickel, molybdenum, zinc, tantalum, copper, aluminum, phosphorus, tungsten, tin, arsenic and titanium (which may be in any form of metal, alloy, oxide, nitride, sulfide, etc.). Examples of the chromate treatment layer include a chromate treatment layer treated with an aqueous solution of chromic anhydride or potassium dichromate, a chromate treatment layer treated with a treatment solution containing chromic anhydride or potassium dichromate and zinc, and the like.

[0098] The chromate treatment layer can be formed by a known method such as immersion chromate treatment, electrolytic chromate treatment, etc. These conditions are not particularly limited, and for example, the conditions for forming a common chromate treatment layer are as follows. Furthermore, the chromate treatment may be performed once or multiple times.

[0099] Chromate solution composition: 1-10 g / L K2Cr2O7, 0.01-10 g / L Zn

[0100] Chromate solution pH: 2-5

[0101] Chromate solution temperature: 30~55℃

[0102] Electrolysis conditions: current density 0.1~10A / dm 2 , Time 0.1 to 5 seconds (in the case of electrolytic chromate treatment)

[0103] The silane coupling treatment layer is not particularly limited, and can be formed of a material known in the technical field.

[0104] Here, in the present specification, "silane coupling treatment layer" means a layer formed of a silane coupling agent.

[0105] The silane coupling agent is not particularly limited, and any silane coupling agent known in the technical field can be used. Examples of the silane coupling agent include amino silane coupling agents, epoxy silane coupling agents, mercapto silane coupling agents, methacryloxy silane coupling agents, vinyl silane coupling agents, imidazole silane coupling agents, triazine silane coupling agents, etc. Among them, amino silane coupling agents and epoxy silane coupling agents are preferred. The above silane coupling agents can be used alone or in combination of two or more.

[0106] A typical method for forming the silane coupling treatment layer is to apply a 1 to 3 volume % aqueous solution of the above-mentioned silane coupling agent and then dry the solution to form the silane coupling treatment layer.

[0107] The copper foil is not particularly limited, and may be either an electrolytic copper foil or a rolled copper foil.

[0108] Electrolytic copper foil is usually produced by electrolytically depositing copper from a copper sulfate plating bath onto a titanium or stainless steel drum, and has a flat S surface (polished surface) formed on the drum side and an M surface (matte surface) formed on the opposite side of the S surface. The M surface of the electrolytic copper foil usually has tiny concavoconvex parts. In addition, the S surface of the electrolytic copper foil has tiny concavoconvex parts because the grinding stripes of the drum formed during grinding are transferred.

[0109] The rolled copper foil has oil pits formed by rolling oil during rolling, so the surface has minute irregularities.

[0110] The material of the copper foil is not particularly limited. When the copper foil is a rolled copper foil, high-purity copper such as refined copper (JIS H3100 alloy number C1100) or oxygen-free copper (JIS H3100 alloy number C1020 or JIS H3510 alloy number C1011) commonly used for circuit patterns of printed wiring boards can be used. In addition, for example, copper alloys such as Sn-doped copper, Ag-doped copper, copper alloys added with Cr, Zr or Mg, and Casson-based copper alloys added with Ni and Si can also be used. In addition, in this specification, "copper foil" is a concept that also includes copper alloy foil.

[0111] In the case where the copper foil is a rolled copper foil, the rolled copper foil may have the following composition: containing 99.0% by mass or more of Cu and 0.003% to 0.825% by mass of one or more elements selected from the group consisting of P, Ti, Sn, Ni, Be, Zn, In and Mg, and the remainder is composed of inevitable impurities. In addition, the rolled copper foil may have the following composition: containing 99.9% by mass or more of Cu and 0.0005% to 0.0220% by mass of P, and the remainder is composed of inevitable impurities. Furthermore, the rolled copper foil may have the following composition: containing 99.0% by mass or more of Cu, and the remainder is composed of inevitable impurities.

[0112] Moreover, when the copper foil is a rolled copper foil, the average crystal grain size may be 0.5 to 4.0 μm, and the tensile strength in the rolling direction may be 235 to 290 MPa.

[0113] Furthermore, the rolled copper foil may have an electrical conductivity of 75% IACS or more. The electrical conductivity of the copper foil can be measured at room temperature (25° C.) by a four-probe method in accordance with JIS H0505 (1975).

[0114] The thickness of the copper foil is not particularly limited, and may be, for example, 1 to 1000 μm, 1 to 500 μm, 1 to 300 μm, 3 to 100 μm, 5 to 70 μm, 6 to 35 μm, or 9 to 18 μm.

[0115] The surface treated copper foil having the above-mentioned structure can be manufactured by a method known in the art. Here, the surface property parameters such as Vmc of the surface treated layer can be controlled by adjusting the formation conditions of the surface treated layer, especially the formation conditions of the roughening treated layer.

[0116] The surface treated copper foil of the embodiment of the present invention controls the Vmc of the surface treated layer to 0.35 to 0.55 μm 3 / μm 2 , so the adhesion with the resin substrate, especially the resin substrate suitable for high-frequency applications, can be improved.

[0117] A copper-clad laminate according to an embodiment of the present invention includes the surface-treated copper foil and a resin base material of a surface-treated layer that adheres to the surface-treated copper foil.

[0118] The copper-clad laminate can be produced by bonding a resin substrate to the surface-treated layer of the surface-treated copper foil.

[0119] The resin substrate is not particularly limited, and any resin substrate known in the technical field can be used. Examples of the resin substrate include paper-based phenolic resin, paper-based epoxy resin, synthetic fiber cloth-based epoxy resin, glass cloth-paper composite-based epoxy resin, glass cloth-glass non-woven composite-based epoxy resin, glass cloth-based epoxy resin, polyester film, polyimide resin, liquid crystal polymer, fluororesin, etc. Among them, the resin substrate is preferably a polyimide resin.

[0120] In addition, as a resin substrate particularly suitable for high-frequency applications, a resin substrate formed of a low-dielectric material can be exemplified. Examples of low-dielectric materials include liquid crystal polymers, low-dielectric polyimides, fluororesins, etc. The low-dielectric material can be, for example, a material having a dielectric constant of 3.5 or less at 1 MHz. As a low-dielectric material suitable for high-frequency applications, a material having a dielectric constant of 3.4 or less at 30 GHz can be used.

[0121] The bonding method between the surface-treated copper foil and the resin substrate is not particularly limited, and can be carried out according to a method known in the art. For example, the surface-treated copper foil and the resin substrate may be laminated and then thermally compressed.

[0122] The copper-clad laminate produced as described above can be used to produce a printed wiring board.

[0123] Since the copper-clad laminate according to the embodiment of the present invention uses the surface-treated copper foil, the adhesion with the resin substrate, especially the resin substrate suitable for high-frequency applications, can be improved.

[0124] A printed wiring board according to an embodiment of the present invention has a circuit pattern formed by etching the surface-treated copper foil of the copper-clad laminate.

[0125] The printed wiring board can be manufactured by etching the surface treated copper foil of the copper clad laminate to form a circuit pattern. The method for forming the circuit pattern is not particularly limited, and known methods such as a subtractive method and a semi-additive method can be used. Among them, the method for forming the circuit pattern is preferably a subtractive method.

[0126] When a printed wiring board is manufactured by a subtractive method, it is preferably carried out in the following manner. First, a resist is applied to the surface of the surface-treated copper foil of the copper-clad laminate, and then exposed and developed to form a specific resist pattern. Then, the surface-treated copper foil of the portion where the resist pattern is not formed (i.e., the unnecessary portion) is etched to remove it to form a circuit pattern. Finally, the resist pattern on the surface-treated copper foil is removed.

[0127] In addition, various conditions in the subtractive method are not particularly limited, and the method can be carried out according to conditions known in the technical field.

[0128] Since the copper-clad laminate described above is used in the printed wiring board according to the embodiment of the present invention, the adhesiveness between the resin substrate, especially the resin substrate suitable for high-frequency applications, and the circuit pattern is excellent.

[0129] [Example]

[0130] Hereinafter, the embodiments of the present invention will be described in more detail by way of examples, but the present invention is not limited to these examples.

[0131] (Example 1)

[0132] A rolled copper foil (HG foil manufactured by JX Metal Co., Ltd.) with a thickness of 12 μm was prepared. After degreasing and pickling on both sides of the copper foil, a roughening treatment layer, a chemical resistance treatment layer (Co-Ni layer), a heat resistance treatment layer (Ni-Zn layer), a chromate treatment layer, and a silane coupling treatment layer were sequentially formed on one side (hereinafter referred to as the "first side") as surface treatment layers, thereby obtaining a surface-treated copper foil. The formation conditions of each treatment layer are as follows.

[0133] (1) Roughening layer / 1st surface

[0134] <Conditions for forming primary roughened particles>

[0135] Bath composition: 12 g / L of Cu, 50 g / L of sulfuric acid, 5 ppm of tungsten (from sodium tungstate dihydrate)

[0136] Bath temperature: 27 °C

[0137] Electroplating conditions: Current density 39.5 A / dm 2 and time 1.2 seconds

[0138] Number of electroplating treatments: 2 times

[0139] <Formation conditions of the covering coating>

[0140] Bath composition: 20 g / L of Cu, 100 g / L of sulfuric acid

[0141] Bath temperature: 50 °C

[0142] Electroplating conditions: Current density 9.6 A / dm 2 and time 1.8 seconds

[0143] Number of electroplating treatments: 2 times

[0144] <Formation conditions of the 2 - time roughened particles>

[0145] Bath composition: 15.5 g / L of Cu, 7.5 g / L of Co, 9.5 g / L of Ni

[0146] Bath temperature: 50 °C

[0147] Electroplating conditions: Current density 33.3 A / dm 2 and time 0.55 seconds

[0148] Number of electroplating treatments: 2 times

[0149] (2) Chemical - resistant treatment layer / First side

[0150] <Formation conditions of the Co - Ni layer>

[0151] Bath composition: 3 g / L of Co, 13 g / L of Ni

[0152] Bath pH: 2.0

[0153] Bath temperature: 50 °C

[0154] Electroplating conditions: Current density 4.5 A / dm 2 and time 0.48 seconds

[0155] Number of electroplating treatments: 1 time

[0156] (3) Heat - resistant treatment layer / First side

[0157] <Formation Conditions of Ni-Zn Layer>

[0158] Composition of plating solution: 23.5 g / L of Ni, 4.5 g / L of Zn

[0159] pH of plating solution: 3.6

[0160] Temperature of plating solution: 40 °C

[0161] Electroplating conditions: Current density 0.7 A / dm 2 and time 0.90 seconds

[0162] Number of electroplating treatments: 1 time

[0163] (4) Chromate treatment layer / First side

[0164] <Formation Conditions of Electrolytic Chromate Treatment Layer>

[0165] Composition of chromate solution: 3 g / L of K2Cr2O7, 0.33 g / L of Zn

[0166] pH of chromate solution: 3.7

[0167] Temperature of chromate solution: 55 °C

[0168] Electrolysis conditions: Current density 1.2 A / dm 2 and time 0.90 seconds

[0169] Number of chromate treatments: 2 times

[0170] (5) Silane coupling treatment layer / First side

[0171] A 1.2 vol% aqueous solution of N-2-(aminoethyl)-3-aminopropyltrimethoxysilane was coated and dried to form a silane coupling treatment layer.

[0172] (Example 2)

[0173] In the formation conditions of the roughened particles for 1 time, the electroplating conditions were changed to a current density of 43.7 A / dm 2 , and in the formation conditions of the covering coating, the electroplating conditions were changed to a current density of 12.3 A / dm 2 and time 1.8 seconds. Otherwise, a surface-treated copper foil was obtained under the same conditions as in Example 1.

[0174] (Example 3)

[0175] In the formation conditions of the heat-resistant treatment layer (Ni-Zn layer) on the first side, the electroplating conditions were changed to a current density of 0.5 A / dm 2 and time 0.90 seconds. Otherwise, a surface-treated copper foil was obtained under the same conditions as in Example 1.

[0176] (Example 4)

[0177] No heat-resistant treatment layer was formed on the first surface, and the electroplating conditions were changed to a current density of 3.0 A / dm in the formation conditions of the chemical-resistant treatment layer (Co-Ni layer). 2 , a surface-treated copper foil was obtained under the same conditions as in Example 1 except for the above.

[0178] (Example 5)

[0179] No heat-resistant treatment layer was formed on the first surface, and the electroplating conditions were changed to a current density of 35.2 A / dm in the formation conditions of the primary roughened particles. 2 , and in the formation conditions of the chemical resistant treatment layer (Co-Ni layer), the electroplating conditions were changed to a current density of 3.0A / dm 2 , a surface-treated copper foil was obtained under the same conditions as in Example 1 except for the above.

[0180] (Example 6)

[0181] No heat-resistant treatment layer was formed on the first surface, and the electroplating conditions were changed to a current density of 42.9 A / dm in the formation conditions of the primary roughened particles. 2 , and in the formation conditions of the chemical resistant treatment layer (Co-Ni layer), the electroplating conditions were changed to a current density of 3.0A / dm 2 , a surface-treated copper foil was obtained under the same conditions as in Example 1 except for the above.

[0182] (Example 7)

[0183] No heat-resistant treatment layer was formed on the first surface, and the electroplating conditions were changed to a current density of 46.7 A / dm in the formation conditions of the primary roughened particles. 2 , and in the formation conditions of the chemical resistant treatment layer (Co-Ni layer), the electroplating conditions were changed to a current density of 3.0A / dm 2 , a surface-treated copper foil was obtained under the same conditions as in Example 1 except for the above.

[0184] (Example 8)

[0185] No heat-resistant treatment layer was formed on the first surface, and the electroplating conditions were changed to a current density of 28.9 A / dm in the formation conditions of the secondary roughened particles. 2 , and in the formation conditions of the chemical resistant treatment layer (Co-Ni layer), the electroplating conditions were changed to a current density of 3.0A / dm 2 , a surface-treated copper foil was obtained under the same conditions as in Example 1 except for the above.

[0186] (Example 9)

[0187] No heat-resistant treatment layer was formed on the first surface, and the electroplating conditions were changed to a current density of 37.7 A / dm in the formation conditions of the secondary roughened particles. 2 , and in the formation conditions of the chemical resistant treatment layer (Co-Ni layer), the electroplating conditions were changed to a current density of 3.0A / dm 2 , a surface-treated copper foil was obtained under the same conditions as in Example 1 except for the above.

[0188] (Example 10)

[0189] No heat-resistant treatment layer was formed on the first surface, and the electroplating conditions were changed to a current density of 42.1 A / dm in the formation conditions of the secondary roughened particles. 2 , and in the formation conditions of the chemical resistant treatment layer (Co-Ni layer), the electroplating conditions were changed to a current density of 3.0A / dm 2 , a surface-treated copper foil was obtained under the same conditions as in Example 1 except for the above.

[0190] (Comparative Example 1)

[0191] A rolled copper foil (HG foil manufactured by JX Metal Co., Ltd.) having a thickness of 12 μm was prepared, and after both sides were degreased and pickled, a roughening treatment layer, a chemical resistance treatment layer (Co-Ni layer), a heat resistance treatment layer (Ni-Zn layer), a chromate treatment layer, and a silane coupling treatment layer were sequentially formed on one side (the first side) as surface treatment layers, thereby obtaining a surface-treated copper foil. The formation conditions of each treatment layer are as follows.

[0192] (1) Roughening layer / 1st surface

[0193] <Conditions for forming primary roughened particles>

[0194] Plating solution composition: 12g / L Cu, 50g / L sulfuric acid, 5ppm tungsten (from sodium tungstate dihydrate)

[0195] Bath temperature: 27°C

[0196] Electroplating conditions: current density 46A / dm 2 , time 1.2 seconds

[0197] Electroplating times: 2 times

[0198] <Conditions for forming the overlay plating layer>

[0199] Plating solution composition: 20g / L Cu, 100g / L sulfuric acid

[0200] Bath temperature: 50°C

[0201] Electroplating conditions: current density 9.6A / dm 2, Electroplating treatment times at 1.8 seconds: 2 times

[0202] (2) Chemical-resistant treatment layer / First side

[0203] <Formation conditions of Co-Ni layer>

[0204] Bath composition: 3 g / L of Co, 13 g / L of Ni

[0205] Bath pH: 2.0

[0206] Bath temperature: 50 °C

[0207] Electroplating conditions: Current density 4.5 A / dm 2 , Electroplating treatment times at 0.48 seconds: 1 time

[0208] (3) Heat-resistant treatment layer / First side

[0209] <Formation conditions of Ni-Zn layer>

[0210] Bath composition: 23.5 g / L of Ni, 4.5 g / L of Zn

[0211] Bath pH: 3.6

[0212] Bath temperature: 40 °C

[0213] Electroplating conditions: Current density 0.9 A / dm 2 , Electroplating treatment times at 0.90 seconds: 1 time

[0214] (4) Chromate treatment layer / First side

[0215] <Formation conditions of electrolytic chromate treatment layer>

[0216] Chromate solution composition: 3 g / L of K2Cr2O7, 0.33 g / L of Zn

[0217] Chromate solution pH: 3.7

[0218] Chromate solution temperature: 55 °C

[0219] Electrolysis conditions: Current density 1.2 A / dm 2 , Time 0.90 seconds

[0220] Chromate treatment times: 2 times

[0221] (5) Silane coupling treatment layer / First side

[0222] Coat a 1.2 vol% aqueous solution of N-2-(aminoethyl)-3-aminopropyltrimethoxysilane and dry it to form a silane coupling treatment layer.

[0223] (Comparative Example 2)

[0224] A rolled copper foil with a thickness of 12 μm (HG foil manufactured by JX Metals Co., Ltd.) was prepared. After degreasing and pickling both sides, a surface treatment layer was formed on one side (the first side) in sequence with a roughening treatment layer, a chemical-resistant treatment layer (Co-Ni layer), a chromate treatment layer, and a silane coupling treatment layer, thereby obtaining a surface-treated copper foil. The formation conditions of each treatment layer are as follows.

[0225] (1) Roughening treatment layer / the first side

[0226] (Formation conditions of the first roughening particles)

[0227] Bath composition: 12 g / L of Cu, 50 g / L of sulfuric acid

[0228] Bath temperature: 25 °C

[0229] Electroplating conditions: Current density 45 A / dm 2 , time 0.68 seconds

[0230] Number of electroplating treatments: 2 times

[0231] (Formation conditions of the covering coating)

[0232] Bath composition: 20 g / L of Cu, 100 g / L of sulfuric acid

[0233] Bath temperature: 50 °C

[0234] Electroplating conditions: Current density 4.9 A / dm 2 , time 0.77 seconds

[0235] Number of electroplating treatments: 2 times

[0236] (Formation conditions of the second roughening particles)

[0237] Bath composition: 15.5 g / L of Cu, 7.5 g / L of Co, 9.5 g / L of Ni

[0238] Bath temperature: 50 °C

[0239] Electroplating conditions: Current density 31.2 A / dm 2 , time 0.37 seconds

[0240] Number of electroplating treatments: 3 times

[0241] (2) Chemical-resistant treatment layer / the first side

[0242] (Formation conditions of the Co-Ni layer)

[0243] Bath composition: 3 g / L of Co, 13 g / L of Ni

[0244] Plating solution pH: 2.0

[0245] Bath temperature: 50°C

[0246] Electroplating conditions: current density 3.2A / dm 2 , time 0.37 seconds

[0247] Electroplating times: 1 time

[0248] (3) Chromate treatment layer / 1st surface

[0249] <Conditions for forming the electrolytic chromate treatment layer>

[0250] Chromate solution composition: 3g / L K2Cr2O7, 0.33g / L Zn

[0251] Chromate solution pH: 3.7

[0252] Chromate solution temperature: 55°C

[0253] Electrolysis conditions: current density 2.7A / dm 2 , time 0.39 seconds

[0254] Chromate treatment times: 2 times

[0255] (4) Silane coupling treatment layer / first surface

[0256] A silane coupling treatment layer was formed by applying a 1.2 volume % aqueous solution of N-2-(aminoethyl)-3-aminopropyltrimethoxysilane and drying it.

[0257] The following property evaluations were performed on the surface-treated copper foils obtained in the above-mentioned Examples and Comparative Examples.

[0258] <Vmc, Sk and Ssk of the surface treatment layer (first surface)>

[0259] The images were taken using a laser microscope (LEXT OLS4000) manufactured by Olympus Corporation. The images were analyzed using the analysis software of a laser microscope (LEXT OLS4100) manufactured by Olympus Corporation. The Vmc, Sk, and Ssk of the surface treatment layer were measured in accordance with ISO 25178-2:2012. In addition, these measurement results are the average values ​​of the values ​​measured at any 10 locations as the measurement results. The temperature during the measurement was set to 23 to 25°C.

[0260] The main setting conditions in the laser microscope and analysis software are as follows.

[0261] Objective lens: MPLAPON50XLEXT (magnification: 50x, numerical aperture: 0.95, immersion type: air, mechanical barrel length: ∞, cover glass thickness: 0, field of view: FN18)

[0262] Optical zoom ratio: 1x

[0263] Scanning mode: XYZ high precision (height resolution: 60nm, number of pixels of input data: 1024×1024)

[0264] Input image size [pixel count]: 257 μm x 258 μm [1024 x 1024]

[0265] (Since the measurement is performed horizontally, the evaluation length is equivalent to 257 μm)

[0266] DIC: Off

[0267] Multilayer: Off

[0268] Laser Strength: 100

[0269] Offset: 0

[0270] Confocal level: 0

[0271] Beam Diameter Aperture: Off

[0272] Image averaging: 1 time

[0273] Noise Reduction: On

[0274] Uneven brightness correction: On

[0275] Optical Noise Filter: On

[0276] Cut-off value: λc=200μm, λs and λf do not exist

[0277] Filter: Gaussian filter

[0278] Noise Removal: Pre-Assay Processing

[0279] Surface (tilt) correction: implemented

[0280] Brightness: Adjust to a range of 30 to 50

[0281] The lightness is a value that should be appropriately set according to the symmetric color tone of the measurement. The above settings are appropriate values ​​when measuring the surface of the surface-treated copper foil having L* of -69 to -10, a* of 2 to 32, and b* of 2 to 21.

[0282] <Measurement of Hue of Measurement Object>

[0283] MiniScan (registered trademark) EZ Model 4000L manufactured by HunterLab was used as a measuring instrument, and the L*, a* and b* of the CIE L*a*b* colorimetric system were measured in accordance with JIS Z8730:2009. Specifically, the surface to be measured of the surface-treated copper foil obtained in the above-mentioned examples and comparative examples was pressed against the photosensitive part of the measuring instrument, and the measurement was performed while preventing light from entering from the outside. In addition, the measurement of L*, a* and b* was performed based on the geometric condition C of JIS Z8722:2009. In addition, the main conditions of the measuring instrument are as follows.

[0284] Optical system: d / 8°, integrating sphere size: 63.5mm, observation light source: D65

[0285] Measurement method: Reflection

[0286] Illumination diameter: 25.4mm

[0287] Measuring diameter: 20.0mm

[0288] Measurement wavelength and interval: 400~700nm, 10nm

[0289] Light source: Pulse xenon lamp, 1 light / measurement

[0290] Traceability standards: Calibrated based on CIE 44 and ASTM E259 by the National Institute of Standards and Technology (NIST)

[0291] Standard observer: 10°

[0292] In addition, the white brick used as the measurement standard used the following object colors.

[0293] When measured at D65 / 10°, the values ​​in the CIE XYZ colorimetric system are X: 81.90, Y: 87.02, Z: 93.76

[0294] <Peel Strength>

[0295] After the surface treated copper foil (the first side) is laminated to the resin substrate formed by the low dielectric material, a circuit with a width of 3 mm is formed in the MD direction (the length direction of the rolled copper foil). The formation of the circuit is implemented according to the usual method. Then, according to JIS C6471:1995, the strength (MD180° peel strength) when the circuit (surface treated copper foil) is peeled off at a speed of 50 mm / min along the 180° direction (i.e., the MD direction) relative to the surface of the resin substrate is measured. The measurement is carried out 5 times, and its average value is used as the result of the peel strength. If the peel strength is more than 0.60 kgf / cm, it can be said that the adhesion between the circuit (surface treated copper foil) and the resin substrate is good.

[0296] Table 1 shows the results of the above-mentioned property evaluations.

[0297] [Table 1]

[0298]

[0299]

[0300] As shown in Table 1, the Vmc of the surface treatment layer is between 0.35 and 0.55 μm. 3 / μm 2 The surface treated copper foils of Examples 1 to 10 within the range of had higher peel strength than Comparative Examples 1 and 2 in which Vmc of the surface treated layer was outside the specific range.

[0301] Next, the influence of the amount of Zn deposited in the surface treatment layer on the solder heat resistance was studied.

[0302] (Example 11)

[0303] A surface-treated copper foil was obtained under the same conditions as in Example 1 except that the heat-resistant treatment layer was not formed on the first surface and that the immersion was performed without applying a current in the formation conditions of the chromate treatment layer.

[0304] (Example 12)

[0305] No heat-resistant treatment layer was formed on the first surface, and the electroplating conditions were changed to a current density of 0.64 A / dm in the formation conditions of the chromate treatment layer. 2 , a surface-treated copper foil was obtained under the same conditions as in Example 1 except for the above.

[0306] (Example 13)

[0307] No heat-resistant treatment layer was formed on the first surface, and the electroplating conditions were changed to a current density of 1.4 A / dm in the formation conditions of the chromate treatment layer. 2 , a surface-treated copper foil was obtained under the same conditions as in Example 1 except for the above.

[0308] About the surface-treated copper foil obtained in the said Example, Vmc, Sk, Ssk and peel strength were measured in the same manner as above, and the following evaluation was performed.

[0309] <Measurement of Zn Adhesion Amount in Surface Treatment Layer (First Surface)>

[0310] The amount of Zn deposited in the surface treatment layer (first surface) was measured by dissolving the surface treatment layer (first surface) in 20 mass % nitric acid and performing quantitative analysis by an atomic absorption method using an atomic absorption spectrophotometer (manufactured by VARIAN, AA240FS).

[0311] <Solder Heat Resistance>

[0312] After the surface-treated copper foil is laminated to a resin substrate formed of a low-dielectric material, etching is performed in such a way that the surface of the surface-treated copper foil becomes 25 mm × 25 mm. The formation of the circuit is implemented according to the usual method. Then, the sample is placed in a constant temperature and humidity machine and maintained at a temperature of 85°C and a relative humidity of 85% for 48 hours. Thereafter, the sample is floated in a solder tank containing solder at a specific temperature, taken out after 30 seconds, and visually confirmed whether bubbles are generated in the circuit of the sample. In the case where no bubbles are generated in the circuit of the sample, another sample is prepared, the temperature of the solder in the solder tank is increased, and it is confirmed again whether bubbles are generated in the circuit of the sample. This operation is repeated until bubbles are generated in the circuit of the sample. The result of the evaluation is represented by the maximum temperature of the solder in which no bubbles are generated in the circuit of the sample. If the maximum temperature of the solder in which no bubbles are generated in the circuit of the sample is above 290°C, it can be said that the heat resistance of the solder is good.

[0313] [Table 2]

[0314]

[0315] As shown in Table 2, the surface treated copper foils of Examples 11 to 13 have a Vmc of the surface treated layer in the range of 0.35 to 0.55 μm, similarly to the surface treated copper foils of Examples 1 to 10, and therefore have higher peel strength than the surface treated copper foils of Comparative Examples 1 and 2. In addition, the surface treated copper foils of Examples 11 to 13 have a Zn deposition amount of 6 to 200 μm / dm 2 , so the solder heat resistance is also good. In particular, the Zn deposition amount is 82 to 200 μm / dm 2 The solder heat resistance of Examples 12 and 13 is particularly excellent.

[0316] As can be seen from the above results, according to an embodiment of the present invention, a surface-treated copper foil capable of improving adhesion to a resin substrate, especially a resin substrate suitable for high-frequency applications, can be provided. In addition, according to an embodiment of the present invention, a copper-clad laminate having excellent adhesion between a resin substrate, especially a resin substrate suitable for high-frequency applications, and a surface-treated copper foil can be provided. Furthermore, according to an embodiment of the present invention, a printed wiring board having excellent adhesion between a resin substrate, especially a resin substrate suitable for high-frequency applications, and a circuit pattern can be provided.

[0317] Therefore, the embodiments of the present invention can be as follows. [1]

[0319] A surface-treated copper foil comprises a copper foil and a surface-treated layer formed on at least one side of the copper foil.

[0320] The volume Vmc of the solid part of the core part of the surface treatment layer is 0.35 to 0.55 μm 3 / μm 2 . [2]

[0322] The surface-treated copper foil as described in [1], wherein the solid volume Vmc of the core portion is 0.37 to 0.52 μm 3 / μm 2 . [3]

[0324] The surface-treated copper foil as described in [1], wherein the solid volume Vmc of the core portion is 0.38 to 0.45 μm 3 / μm 2 . [4]

[0326] The surface-treated copper foil as described in any one of [1] to [3], wherein the level difference Sk of the core portion of the surface-treated layer is 0.70 to 1.50 μm. [5]

[0328] The surface-treated copper foil as described in any one of [1] to [3], wherein the level difference Sk of the core portion of the surface-treated layer is 0.85 to 1.30 μm. [6]

[0330] The surface-treated copper foil as described in any one of [1] to [3], wherein the level difference Sk of the core portion of the surface-treated layer is 1.03 to 1.18 μm. [7]

[0332] The surface-treated copper foil as described in any one of [1] to [6], wherein the skewness Ssk of the surface-treated layer is 0.10 to 1.00. [8]

[0334] The surface-treated copper foil as described in any one of [1] to [6], wherein the skewness Ssk of the surface-treated layer is 0.30 to 0.90. [9]

[0336] The surface-treated copper foil as described in any one of [1] to [6], wherein the skewness Ssk of the surface-treated layer is 0.45 to 0.80.

[10]

[0338] The surface-treated copper foil as described in any one of [1] to [9], wherein the amount of Zn deposited in the surface-treated layer is 6 to 200 μm / dm 2 .

[11]

[0340] The surface treated copper foil as described in

[10] , wherein the amount of Zn deposited in the surface treated layer is 82 to 200 μm / dm 2 .

[12]

[0342] The surface-treated copper foil as described in any one of [1] to

[11] , wherein the surface-treated layer includes a roughening-treated layer.

[13]

[0344] A copper-clad laminate comprising the surface-treated copper foil as described in any one of [1] to

[12] and a resin substrate adhered to the surface-treated layer of the surface-treated copper foil.

[14]

[0346] A printed wiring board having a circuit pattern formed by etching the surface-treated copper foil of the copper-clad laminate described in

[13] .

[0347] Description of Reference Numerals

[0348] 10: Copper foil

[0349] 20: 1 time coarsening particles

[0350] 30: Covering coating

[0351] 40: Secondary coarsening of particles

Claims

1. A surface-treated copper foil comprising a copper foil and a surface-treated layer formed on at least one side of the copper foil, The volume Vmc of the solid part of the core part of the surface treatment layer is 0.35 to 0.55 μm 3 / μm 2 .

2. The surface-treated copper foil according to claim 1, wherein The volume Vmc of the solid part of the core part is 0.37-0.52 μm 3 / μm 2 .

3. The surface-treated copper foil according to claim 1, wherein The volume Vmc of the solid part of the core part is 0.38 to 0.45 μm 3 / μm 2 .

4. The surface-treated copper foil according to any one of claims 1 to 3, wherein The level difference Sk of the core part of the surface treatment layer is 0.70 to 1.50 μm.

5. The surface-treated copper foil according to any one of claims 1 to 3, wherein The level difference Sk of the core part of the surface treatment layer is 0.85 to 1.30 μm.

6. The surface-treated copper foil according to any one of claims 1 to 3, wherein The level difference Sk of the core part of the surface treatment layer is 1.03 to 1.18 μm.

7. The surface-treated copper foil according to claim 4, wherein: The skewness Ssk of the surface treatment layer is 0.10-1.

00.

8. The surface-treated copper foil according to claim 6, wherein: The skewness Ssk of the surface treatment layer is 0.30 to 0.

90.

9. The surface-treated copper foil according to claim 6, wherein: The skewness Ssk of the surface treatment layer is 0.45 to 0.

80.

10. The surface-treated copper foil according to claim 1, wherein The Zn adhesion amount in the surface treatment layer is 6 to 200 μm / dm 2 .

11. The surface-treated copper foil according to claim 10, wherein: The Zn adhesion amount in the surface treatment layer is 82 to 200 μm / dm 2 .

12. The surface-treated copper foil according to any one of claims 1 to 3, wherein The surface treatment layer includes a roughening treatment layer. 13 . A copper-clad laminate comprising the surface-treated copper foil according to claim 1 , and a resin substrate adhered to the surface-treated layer of the surface-treated copper foil. 14 . A printed wiring board comprising a circuit pattern formed by etching the surface-treated copper foil of the copper-clad laminate according to claim 13 .

Citation Information

Patent Citations

  • Copper foil, and method for producing copper foil

    JP2012112009A